2012
DOI: 10.1139/y2012-129
|View full text |Cite
|
Sign up to set email alerts
|

Chiral recognition of doxazosin enantiomers in 3 targets for therapy as well as adverse drug reactions in animal experiments

Abstract: Doxazosin used in benign prostatic hyperplasia has the side effects of causing hypotension and the risk of heart failure. The 3 targets of α(1A)-adrenoceptors (in the prostate), α(1D)-adrenoceptors (in the aorta), and an unknown mechanism (in the heart) are involved, respectively. We hypothesized that there is a chiral recognition of doxazosin enantiomers in the 3 targets. Using isolated rat aorta (α(1D)-adrenoceptors) and rabbit prostate (α(1A)-adrenoceptors), we examined pA(2) and pK(B) values of doxazosin e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…The pK B value of (±)doxazosin treatment (8.694±0.032) was significantly smaller than that of (+)doxazosin treatment (8.995±0.032), but significantly larger than that of (-)doxazosin treatment (8.032±0.039). Previous studies also obtained similar results when observing the potency of (-)doxazosin, (+)doxazosin, and (±)doxazosin against NA-induced vasoconstriction via α 1 -adrenoceptors in the isolated rat thoracic aorta [11] and mesenteric artery [23] .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The pK B value of (±)doxazosin treatment (8.694±0.032) was significantly smaller than that of (+)doxazosin treatment (8.995±0.032), but significantly larger than that of (-)doxazosin treatment (8.032±0.039). Previous studies also obtained similar results when observing the potency of (-)doxazosin, (+)doxazosin, and (±)doxazosin against NA-induced vasoconstriction via α 1 -adrenoceptors in the isolated rat thoracic aorta [11] and mesenteric artery [23] .…”
Section: Discussionsupporting
confidence: 70%
“…We further reported that (-)doxazosin, (+)doxazosin and (±)doxazosin treatment antagonized noradrenaline (NA)-induced vasoconstriction via α 1 -adrenoceptors in a competitive manner in the rat thoracic aortic ring preparation, and the pA 2 value for (-)doxazosin treatment was markedly less than those for (+)doxazosin and (±)doxazosin [11] . Similar results were confirmed in the isolated common carotid, ear, mesenteric, pulmonary arteries and the thoracic aorta of rabbits [12,13] .…”
Section: Introductionmentioning
confidence: 93%
“…8 The chiral carbon atom in the molecular structure of doxazosin does not affect the therapeutic activity at α 1A -adrenoceptors in the rabbit prostate, but it significantly affects the blocking activity at α 1Dadrenoceptors in the rat aorta. [9][10][11] Moreover, in rat and rabbit heart tissues, (+)-(S)-doxazosin significantly decreases the atrial rate and produces negative inotropic effects; however, (-)-(R)-doxazosin produces positive inotropic effects in the atria via an α 1 -adrenoceptor-independent mechanism. 9 In addition, Liu et al reported that the plasma concentration of (+)-(S)-doxazosin for all the timepoints tested was higher than that of (-)-(R)-doxazosin, and the area under the curve (AUC) of (+)-(S)-doxazosin was 2.3 times higher than that of (-)-(R)-doxazosin after oral administration of therapeutic doses of racemic doxazosin in two healthy volunteers.…”
Section: Abstract: Pharmacokinetics;mentioning
confidence: 99%
“…[4][5][6][7] Doxazosin contains a chiral carbon at the 2-position of the 1, 4-benzodioxan-2-ylcarbonyl ring, consisting of two optical isomers, (+)-(S)-doxazosin and (-)-(R)-doxazosin, and it is used clinically as a racemate. [9][10][11] Moreover, in rat and rabbit heart tissues, (+)-(S)-doxazosin significantly decreases the atrial rate and produces negative inotropic effects; however, (-)-(R)-doxazosin produces positive inotropic effects in the atria via an α 1 -adrenoceptor-independent mechanism. (-)-(R)-doxazosin was shown to decrease the carotid blood pressure more weakly than (+)-(S)doxazosin in anesthetized rats.…”
mentioning
confidence: 99%
See 1 more Smart Citation